دراسة انتشار المقاومة للفلوروكينولونات عند الأمعائيات - يازجي, هيثم; أحمد, آنا (Latakia University Journal -Medical Sciences Series, 2018)
Multidrug resistant (MDR) strains of the Gram-negative pathogenic bacterium, Enterobacteriace, particularly fluoroquinolone-resistant strains, are the major causative agents for hospital acquired (HA) infections, as well as epidemics linked to gastrointestinal (GI), urinary tracts, also pneumonia , abscess, meningitis and sepsis. The prevalence of fluoroquinolone-resistance among 3107 strains of enterobacteriace, isolated from clinical samples of patients with infections caused by enterobacteriace at Al-Assad and Tichreen University Hospitals, Lattakia, Syria, over 6 years (2011-2016) is recorded, along with sensitivity patterns to currently used anti-biotics, including cephalosporins aminoglycosides, pencellins and fluoroquinolones with disc-diffusion method. A total of 3107 strains of enterobacteriace were isolated from the clinical samples, 925 strains of them were fluoroquinolone-resistant (30%) , of which 272 isolates were from CA samples (29%) and 653 isolates were from hospitalized patients HA (71%) during the study period. We found a high prevalence of resistance towards the drugs used as “first-line” when treating UTIs: ampicillin, cotrimoxazole, and ciprofloxacin (90%, 96%, and 32% resistance, respectively) تعتبر الجراثيم سالبة الغرام ذات المقاومة الدوائية المتعددة و خاصةً الأمعائيات المقاومة للفلوروكينولونات من المسببات الرئيسية للإنتانات المكتسبة في المشافي خاصةً الإنتانات المعوية وإنتانات السبيل البولي وغيرها من إنتانات الجروح والتهاب السحايا والالتهاب الرئوي. شملت هذه الدراسة الراجعة (3107) عينة من عزولات الأمعائيات في قسم الأحياء الدقيقة في مشفيي الأسد وتشرين الجامعيين في اللاذقية بين عامي (2011- 2016). والتي أجري لها اختبار الحساسية للصادات بطريقة الانتشار القرصي مع استخدام واحد أو أكثر من عائلة الفلوروكينولونات (السيبروفلوكساسين والليفوفلوكساسين والنورفلوكساسين) من بين ال (3107) عزولة جرثومية كان هناك (925) عزولة جرثومية مقاومة للفلوروكينولونات بنسبة (30%). وكان منها (653) عزولة من مرضى مقيمين للاستشفاء في المشفى مقاومة للفلوروكينولونات بنسبة (71%) و(272) عزولة من مرضى خارج المشفى مقاومة للفلوروكينولونات بنسبة(29%). وجدنا نسبة عالية من المقاومة تجاه الصادات التي تعتبر الخط الأول في علاج إنتانات السبيل البولي: الأمبيسيللين , الكوتريموكسازول, السيبروفلوكساسين ( 90% , 96% , 32% عل التوالي ).